Cardiac fat‐containing lesions are common in tuberous sclerosis complex. Issue 7 (22nd May 2013) - Shaaya, Elias A.; Hirshberg, Jacqueline S.; Rabe, Olivia T.; Thibert, Ronald L.; Inglessis, Ignacio; Sharma, Amita; Thiele, Elizabeth A.
ABSTRACT Tuberous sclerosis complex (TSC) is a highly variable, multisystem, genetic disorder that affects approximately 1:6, 000 individuals. It has previously been thought that the cardiac manifestation of TSC is congenital rhabdomyomas, which occur during infancy and typically regress during childhood. Recently, there have been findings of cardiac fat‐containing lesions in adult TSC patients that appear distinct from the presence of cardiac rhabdomyomas. We review the chest CT scans of 73 individuals with TSC to check for cardiac fat‐containing lesions. Fat‐containing lesions were found in the heart of approximately one‐third of adolescents and adults with TSC. In this population with cardiac fat‐containing lesions, no statistically significant difference was observed between the genders and between the different mutation types. Compared to those without cardiac fat findings, those with cardiac fat were more than twice as likely to have another abdominal manifestation of TSC. The results indicate that it may be appropriate to consider these cardiac fat foci as a clinical criterion for the diagnosis of TSC, given their frequency in our population. Our findings also suggest that a relation exists between the cardiac fat‐containing lesions and other abdominal angiomyolipomas. More research regarding these cardiac fat‐containing lesions is needed to better characterize their origin and clinical significance. © 2013 Wiley Periodicals, Inc.